Evaluation of genetic effect on quality and yield traits of Wxin in rice substitution lines of Y58S by marker-assisted backcross breeding - Sheng, Wentao; Zhou, Lijie; Wu, Jun; Bai, Bin; Deng, Qiyun (The Indian Journal of Genetics and Plant Breeding, 2016)
Y58S is an elite line with superior grain qualities except for the low amylose content (AC). Basmati 370 was used as donor of Wxin with intermediate AC into Y58S by marker assisted backcross breeding. Through repeated backcrossing, three Wxin substitution lines were obtained, which were crossed with 93-11 to produce hybrids. The improved Y58S lines and the hybrids derived from them had significantly increased AC and chalkiness with reduction on gel consistency and the head rice recovery, while the agronomic performance remained same as the parent lines.Changes in eating qualities indicated the Waxy region might have pleiotropic effect on grain traits.